Answer:
See below ~
Step-by-step explanation:
Here, let's apply the resultant vector formula :
![R = \sqrt{A^(2) + B^(2) + 2ABcos\theta}](https://img.qammunity.org/2023/formulas/physics/college/ps47mjrwbi8q20sajaskwinu7m7dupvsrk.png)
Part (i) :
√3P² + Q² = √(P + Q)² + (P - Q)² + 2(P + Q)(P - Q)cosθ
3P² + Q² = P² + Q² + 2PQ + P² + Q² - 2PQ + 2(P² - Q²)cosθ
2(P² - Q²)cosθ = P² - Q²
cosθ = 1/2
θ = π/3 or 60°
Part (ii) :
√2(P² + Q²) = √(P + Q)² + (P - Q)² + 2(P + Q)(P - Q)cosθ
2(P² + Q²) = P² + Q² + 2PQ + P² + Q² - 2PQ + 2(P² - Q²)cosθ
2(P² - Q²)cosθ = 0
cosθ = 0
θ = π/2 or 90°
Part (iii) :
√P² + Q² = √(P + Q)² + (P - Q)² + 2(P + Q)(P - Q)cosθ
P² + Q² = P² + Q² + 2PQ + P² + Q² - 2PQ + 2(P² - Q²)cosθ
2(P² - Q²)cosθ = -P² - Q²
cosθ =
![(-(P^(2)+ Q^(2)) )/(2(P^(2)-Q^(2)) )](https://img.qammunity.org/2023/formulas/physics/college/5gqrrbeeanux2b21o95jzn1nu36utw2gxo.png)
![\theta = cos^(-1) (-(P^(2)+ Q^(2)) )/(2(P^(2)-Q^(2)) )](https://img.qammunity.org/2023/formulas/physics/college/x29t86eaj8kaqzwcdfyuicfgks2ojyw5wp.png)